Strategi Sekolah dalam Membina Hubungan dengan Orang Tua Siswa Guna Meningkatkan Prestasi Belajar Siswa - Syafik Ubaidilla; Ahmad Masrukin (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
Parents generally do not know and are fully aware of the responsibility for their children's education at school. Most parents believe that the education of their children is solely the responsibility of the teacher at school. This view was eroded by SDN Kedungsoko 2 Sukomoro Nganjuk. He implements the school's strategy in fostering relationships with parents to improve learning achievement. The research method used in this study is the qualitative approach. This study found that the school's strategy in fostering relationships with parents to improve student achievement is based on a reasonable and correct educational program, which is balanced, comprehensive, sustainable, honest, and following reality, easy to understand and evaluate.